Effect of pH on the structural and optical properties of nanostructured CdO films grown by chemical bath deposition technique. (1st December 2014) - Ismail, Raid A.; Ahmed, Hani H.; Al‐Samarai, Abdul‐Majeed E.; Mohmed, Sabre J.
Abstract : Nanostructured cadmium oxide (CdO) thin films have been deposited on glass substrates using the chemical bath deposition (CBD) technique at different pH values. To obtain good film stoichiometry, the heating of films in static air at a temperature of 573 K for 3 h was carried out. X‐ray diffraction and atomic force microscope investigations confirmed the cubic structure of the deposited CdO films. Films prepared with pH = 12.4 are almost homogeneous and consisted of nanowires with diameters of less than 100 nm. The optical properties showed that the CdO films prepared have an average optical transmittance of ∼86% and the optical bandgap varied from 2.38 to 2.57 eV for pH solutions of 10.2 and 12.4, respectively. The effect of pH on the film thickness, grain size and root‐mean square of roughness was investigated and analysed.